2007
DOI: 10.1038/sj.bjc.6603848
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus-16 is integrated in lung carcinomas: a study in Chile

Abstract: The human papillomavirus (HPV) was detected in 20 (29%) out of 69 lung carcinomas (LCs) in Chile, by PCR and Southern blot, and was more frequently detected in squamous cell carcinoma (SQC) than in adenocarcinomas (46 vs 9%, P ¼ 0.001). HPV-16, positive in 11 cases, was the most frequently detected HPV genotype determined by DNA sequencing. HPV-16 E2/E6 ratio, estimated from real-time PCR analysis, was much lower than the unity, suggesting that at least a partial HPV-16 genome was integrated in all but one HPV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 40 publications
3
57
1
1
Order By: Relevance
“…The present study also showed that HPV-16 detected in lung carcinomas are frequently integrated, confirming the finding of our previous report examining lung carcinomas in Chile (12). However, the following three points should be taken into account: i) disrupted viral copies may be flanked by intact viral copies (40), ii) HPV integration does not always cause E2 disruption (41,42); and iii) more than a 10-fold excess of episomal form to integrated form of the virus interferes with E2 amplification, regardless the amount of viral DNA, resulting in lower E2/E6 ratios (43).…”
Section: ------------------------------------------------------------supporting
confidence: 93%
See 1 more Smart Citation
“…The present study also showed that HPV-16 detected in lung carcinomas are frequently integrated, confirming the finding of our previous report examining lung carcinomas in Chile (12). However, the following three points should be taken into account: i) disrupted viral copies may be flanked by intact viral copies (40), ii) HPV integration does not always cause E2 disruption (41,42); and iii) more than a 10-fold excess of episomal form to integrated form of the virus interferes with E2 amplification, regardless the amount of viral DNA, resulting in lower E2/E6 ratios (43).…”
Section: ------------------------------------------------------------supporting
confidence: 93%
“…On the other hand, the etiological significance of HPV in lung carcinogenesis is yet unclear. Interestingly, however, HPV integration in the host genome has been reported in lung carcinomas (12). The expressions of HPV E6 and E7 genes, important HPV oncogenes, are regulated by HPV E2 gene, whose disruption is caused by HPV genome integration into the host genome.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, real-time PCR was used in 27 samples to confirm the presence of HPV-16. E 2 was not found in 59.3% (16/27) of the samples, suggesting that at least a partial HPV-16 genome was integrated into the host genome, which is similar to the 66.7% reported in Chile (31) .…”
Section: Discussionsupporting
confidence: 79%
“…It would have been interesting, for instance, to assess whether the transcriptionally inactive integrant with a VL of 10 2 identified in a clinical samples [57] was silent because of epigenetic suppression or for other reasons such as loss of the viral promoter. Remarkably, transgenic mice showed the lowest proportion of actively transcribing proviruses, clearly indicating that despite bearing at least one copy of integrated virus in each cell, the viral genetic expression was modulated by the cellular environment; epigenetic mechanisms were evoked to explain the transcriptional silencing [53,54].…”
Section: 2217/fvl-2017-0063mentioning
confidence: 99%
“…The reactivation of the virus was postulated to be dependent on protein kinase C (PKC): TPA is a direct stimulator of PKC and PKC is also activated by increased intracellular calcium levels. No infectious HHV-6 particles were produced after reactivation.Overall the viral load (VL) of the samples gathered in the present study ranged between 10 −7 and 10 3 copies per cell [35,57] 1982 1984 1985 1986 1987 1988 1989 1992 1994 1995 1997 1998 1999 2000 2002 2003 2004 2006 2007 2008 2009 2011 2013 2014 2015 2016 Remarkably, an HPV integrant with 217 copies was reported being transcriptionally silent; it was not indicated whether the HPV sequences were dispersed in more than one integration site [57]. The data regarding the integration sites were limited and did not provide information regarding a possible association between the targeted locus and transcriptional status of the provirus; neither was present a description of the chromatin context of the targeted loci.…”
mentioning
confidence: 99%